Properties of virgin coconut oil extracted through the fermentative aqueous process with post-heat treatment - Caintic, Ma. Aissa Isiderio; Ciron, Christian E. (2006)
ABSTRACT Virgin coconut oil (VCO) was produced through the fermentative aqueous process with post-heat treatment. The influence of different post-heat treatment temperatures (60°C, 80°C, 100°C) on the oil was evaluated qualitatively and quantitatively. Temperature differences did not affect yield, initial free fatty acids (FFA) content, moisture and volatile matter (MVM) content, and sensory characteristics of the extracted VCO. However, the percentage increase in FFA content after three months of storage was lowest for the VCO heat-treated at 80°C, so this temperature was chosen for process standardization. The VCO produced was characterized based on its physicochemical and sensory properties. These properties were compared with the standard specifications for VCO and refined, bleached and deodorized (RBD) coconut oil to evaluate if they fell within the allowable limits. The extracted VCO did not deviate from all of the standard physico-chemical requirements tested, except for specific gravity which was a little higher in this case. Other properties of the produced oil such as refractive index, moisture and volatile matter content, saponification value, iodine number, peroxide value, color and FFA content, were within the tolerable ranges given in the standards. Sensory evaluation using attribute scoring characterized the VCO sample as colorless and clear, with perceptible nutty/latik/coco jam aroma, and barely perceptible acid and rancid aroma. The moisture sorption isotherm of the fermentative aqueous processed VCO samples was also constructed using the Proximity Equilibrium Cell (PEC) method, and its monolayer value was also obtained using the Brunauer-Emmet-Teller (BET)equation. Maximum stability of the VCO samples was found to be within the water activity range of 0.09 to 0.88 wherein its equilibrium moisture content at dry basis is 0.03% to 0.18%. The monolayer value obtained was 0.0168 grams of water per gram of the dry VCO sample, which is the maximum amount of water that can be very strongly bound to the dry samp
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Virgin coconut oil